Legal Deposit of Digital Materials - Oltmans, Erik (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Digital publishing is causing a real paradigm shift for research institutions and publishers, as well as for libraries. As a consequence these institutions have to develop new policies, new business models and new infrastructures and techniques. A major problem is that, at the same rate at which our world is becoming digital, the digital information is threatened. New types of hardware, computer applications and file formats supersede each other, making our recorded digital information inaccessible in the long-term. In the past years libraries and archives have undertaken several actions and studies on digital preservation issues. For instance the Koninklijke Bibliotheek (KB) has jointly with IBM developed a standard-based deposit system: Digital Information Archiving System ( DIAS). Using DIAS the KB realised in 2002 an electronic deposit (the e-Depot) and signed archiving agreements with major science publishers for permanent keeping of their digital materials. In this paper I will discuss the fully operational e-Depot at the KB. I will focus on the data flow of processing the digital publications, and I will address the issue of digital preservation in detail.